2011
DOI: 10.1093/imrn/rnr219
|View full text |Cite
|
Sign up to set email alerts
|

Lower Bounds on Odd Order Character Sums†

Abstract: Abstract.A classical result of Paley shows that there are infinitely many quadratic characters χ (mod q) whose character sums get as large as √ q log log q; this implies that a conditional upper bound of Montgomery and Vaughan cannot be improved. In this paper, we derive analogous lower bounds on character sums for characters of odd order, which are best possible in view of the corresponding conditional upper bounds recently obtained by the first author.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 4 publications
1
18
0
Order By: Relevance
“…under the assumption of GRH. Shortly afterwards, Goldmakher and Lamzouri [10] proved that this bound is, in fact, optimal. More precisely, they showed that for any > 0 and any fixed odd integer g 3, there exist arbitrarily large q and primitive characters χ (mod q) of order g satisfying M(χ) g, √ q(log log q) (g/π ) sin (π/g)− .…”
Section: Youness Lamzourimentioning
confidence: 99%
See 2 more Smart Citations
“…under the assumption of GRH. Shortly afterwards, Goldmakher and Lamzouri [10] proved that this bound is, in fact, optimal. More precisely, they showed that for any > 0 and any fixed odd integer g 3, there exist arbitrarily large q and primitive characters χ (mod q) of order g satisfying M(χ) g, √ q(log log q) (g/π ) sin (π/g)− .…”
Section: Youness Lamzourimentioning
confidence: 99%
“…Let z = (log Q) 10 . Then it follows, from Proposition 2.4, that, for all but at most Q 1/4 fundamental discriminants d with 0 < εδd < Q…”
Section: Y Lamzourimentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it would also be nice to be able to construct a family of characters χ (mod q) so that S(χ, r) is large, as is done by Paley [13] in the case r = 1. See also [8] and [10] for an improvement of Paley's result.…”
Section: Open Questionsmentioning
confidence: 99%
“…No other unconditional lower bounds were proved until quite recently, when the authors [3] established that there are arbitrarily large q and primitive characters χ (mod q) of fixed odd order g such that…”
Section: Introductionmentioning
confidence: 99%